(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Papaya (Carica Papaya) also known as ‘pawpaw’, is pulpy fruit of a large plant of family Caricaceae. Carica Papaya seeds, ripe, leaves and unripe fruit are used as traditional medicine, also considered as nutraceutical fruit due to its multifaceted medicinal properties. It has a high content of Vit. A, B, and C. The plant of Carica Papaya has versatile biological function and pharmacological activity such as anti-inflammatory antioxidant, diuretic, hypoglycemic, anthelminthic activity. In the latex of Carica Papaya, the present enzyme ‘papain’ useful for industrial utilization and of high research interest. Other, Chymopapain having antiviral, antifungal properties. Nearby industrial areas of Khetri, Jhunjhunu, Rajasthan samples of Carica Papaya seeds germinated, accumulated and utilized for assimilating and finding metals. By using Soxhlet apparatus oil extracted and heavy metals were detected by Atomic Absorption Spectroscopy (AAS). This technique (AAS) was used for the finding and confirmation of trace metals (Cd, Cr, Co, Fe, Zn, Pb and Ni) stored in Carica Papaya seed oil. The following trace metals concentration were obtained (mg/100g) Cr (2.78), Fe (1.91), Pb (1.43), Cd (0.82), Cu (1.48), Ni (1.23), Co (0.99), and Zn (0.79).Among the other major environmental contaminants the obtained trace metals created a major threat to human and animal health by their long time presence. During analysis of GC–FID (Gas Chromatography Flame Ionization Detection), Oleic (49.20%), Linoleic acid (36.99%), Palmitic acid (6.07%), Stearic acid (3.49%), Linolenic acid (0.78%), Behenic acid (0.62%), Palmitoleic acid (0.29%), Arachidic acid (0.27%), were found to be present in Carica Papaya seed oil. Oleic acid was also found as a major fatty acid. Carica Papaya is one of the naturally gifted plants which in turn stop and decrease different type of diseases& illnesses.